2018
DOI: 10.1111/cpr.12476
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of autophagy with apoptosis in alveolar epithelial cells contributes to chronic pulmonary toxicity induced by methamphetamine

Abstract: Concurrence of autophagy with apoptosis in alveolar epithelial cells contributes to chronic pulmonary toxicity induced by MA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…METH-induced apoptosis of alveolar epithelium cells is mediated by endoplasmic reticulum stress 30 , resulting in the reduction of pulmonary alveoli. Concurrence of autophagy with apoptosis in alveolar epithelial cells contributes to chronic pulmonary toxicity induced by chronic METH use 31 . Also, we previously demonstrated that pharmacological levels of METH in human blood and organs are cytotoxic to ∼ 20% of the phagocytes 32 .…”
Section: Discussionmentioning
confidence: 99%
“…METH-induced apoptosis of alveolar epithelium cells is mediated by endoplasmic reticulum stress 30 , resulting in the reduction of pulmonary alveoli. Concurrence of autophagy with apoptosis in alveolar epithelial cells contributes to chronic pulmonary toxicity induced by chronic METH use 31 . Also, we previously demonstrated that pharmacological levels of METH in human blood and organs are cytotoxic to ∼ 20% of the phagocytes 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The autophagy protein microtubule-associated protein 1 light-chain 3 (LC3) exists in two forms during activation of autophagy (Fu et al, 2016). After LC3 is cleaved to LC3 I by Atg4 in the cytoplasm, phosphatidylethanolamine (PE) and LC3 I form a LC3-II-PE complex, which participates in autophagic membrane extension and is distributed on the membranes of autophagic vacuoles (Yun et al, 2018). Integration of the LC3-II-PE complex and SQSTM1(p62) transfers the wasted substance, which is degraded by autolysosomes, into autophagosomes (Katsuragi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian target of rapamycin (mTOR) is universally acknowledged as an inhibitor of autophagy, so that autophagy will occur after mTOR is inactivated 8 . Our previous studies found that MA‐induced inactivation of mTOR promoted autophagy‐mediated alveolar epithelial injury 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 Our previous studies found that MA-induced inactivation of mTOR promoted autophagy-mediated alveolar epithelial injury. 9 Senescence is the complex process of deterioration that occurs over the lifetime of an organism, resulting in progressive functional decline and eventual death. 10 Cellular senescence is a phenomenon that the cells lose the ability of self-proliferation.…”
mentioning
confidence: 99%
See 1 more Smart Citation